Effects of In Ovo Vitamin E–Selenium Administration on Hatchability, Chick Quality, and Post-Hatch Growth Performance of Japanese Quail Exposed to Cyclic Heat Stress - Kurdman M. Sulaiman (Universitas Airlangga, 2026)
Heat stress impairs embryonic development, hatchability, growth, and antioxidant defense in poultry. Vitamin E and selenium are complementary antioxidants that may improve performance under stressful conditions. This study evaluated in ovo injection of vitamin E–selenium on hatchability, chick quality, blood biochemistry, thyroid hormones, and post-hatch growth of Japanese quail exposed to cyclic heat stress (35°C, 60% relative humidity, 8 h/day). A total of 620 fertile eggs were incubated, and on day 14 viable eggs were allocated to five groups (100 each): a non-injected control, a distilled-water control (0.02 mL), and three groups injected with 0.01, 0.02, or 0.03 mL vitamin E–selenium into the amniotic cavity. All treated groups showed significantly higher hatchability than controls (P < 0.05), increasing from 76.54% to 83.78%, while embryonic mortality fell from 23.46% to 16.22%. At 35 days, final body weight rose from 145.21 g to 150.91 g, and feed conversion ratio improved from 2.63 to 2.47 (P < 0.05). Serum total protein, albumin, globulin, and thyroid hormones (T3, T4) were unaffected (P > 0.05). In ovo vitamin E–selenium enhances hatchability and post-hatch growth of heat-stressed quail without adversely affecting blood biochemical or endocrine parameters, indicating a practical strategy under heat stress.